Mechanistic modeling of glycerol fermenting and sulfate-reducing processes by granular sludge under sulfidogenic conditions. Issue 3 (June 2022) - Zhou, X.; Dorado, A.D.; Lafuente, J.; Gamisans, X.; Gabriel, D.
Abstract: Glycerol can be converted to ethanol, 1, 3-propanediol, formate, acetate, propionate, and inorganic carbon under anaerobic conditions through oxidative and reductive pathways in the absence and presence of sulfate. A structured mathematical model considering multiple pathways of glycerol fermentation combined with sulfate reduction was set up in this work, where three mechanisms were proposed and verified by modeling. Finally a mechanism properly predicting both glycerol fermenting and sulfate-reducing processes was chosen. Concentrations of multiple intermediates measured in batch activity tests were satisfactorily described by the model. The intermediate products of glycerol fermentation included formate, propionate, ethanol, 1, 3-propanediol, and 3-hydroxypropionate (3HP). The main pathways of glycerol fermentation were the oxidative pathway to produce ethanol and the reductive pathway to produce 1, 3-propanediol. The former accounted for 40.6% of the total glycerol converted whereas the latter accounted for 42.6%. 1, 3-propanediol was converted to 3HP coupled to sulfate reduction. 3HP was mainly further oxidized to acetate. The kinetic parameters of maximum specific uptake rates of substrate were calibrated and then, the sulfate reduction process was validated. The confidence intervals of estimated parameters were assessed according to the Fisher information matrix (FIM) method. The low confidence intervals obtained indicated that the experimental behavior was satisfactorily described with the proposed kinetic model. Graphical Abstract: ga1 Highlights: A mathematical model of glycerol fermentation with sulfate reduction was established. Glycerol fermentation & sulfate reduction parameters were calibrated. Three mechanisms considering multiple pathways of glycerol fermentation were proposed & verified. The main pathways of glycerol fermentation produced ethanol and 1, 3-propanediol. 3-hydroxypropionate was also an intermediate product of glycerol degradation & 1, 3-propanediol oxidation.